Parental Skills, Assortative Mating, and the Incidence of Autism Spectrum Disorder - N. Meltem Daysal; Todd E. Elder; Judith K. Hellerstein; Scott A. Imberman; Chiara Orsini (Institute of Labor Economics (IZA), 2021)
We use rich administrative data from Denmark to assess medical theories that autism spectrum disorder (ASD) is a heritable condition transmitted through underlying parental skills. Positing that occupational choices reflect skills, we create two separate occupation-based skill measures and find that these measures are associated with ASD incidence among children, especially through the father's side. We also assess the empirical relevance of assortative mating based on skill, concluding that intertemporal changes in assortative mating explain little of the increase in ASD diagnoses in recent decades.
Keywords: I1; J1; 330; parental skills; autism